STUDY OF THE STYLE FEATURES OF THE LITERARY WORKS WITH THE HELP OF IMAGES OF NATURAL ELEMENTS DURING THE LESSONS OF UKRAINIAN LITERATURE IN 10-11 GRADES - Orishchenko, Іnna (International Journal of Innovative Technologies in Social Science, 2020)
The article is devoted to the problem of studying of the style features of the literary works with the help of images of the natural elements during the lessons of Ukrainian literature in 19-11 grades. In this paper, a new method of studying of the style features is presented. The author of the article defines the aim and basic methodological principles of the research. The aim of the study is to create a theoretical and methodological system that will explore the main stylistic characteristics of the work with the help of images of water, fire, air and earth. The main goal of this research is to analyze the nature of the links between the images of natural elements and stylistic features of a literary work and to develop a methodological system that would allow exploring different levels of the work of art effectively. The images of natural elements play a vital role in studying different levels of the literary works. Previous studies indicate the insignificant role of images of water, fire, air and earth to reveal the stylistic features of the artistic text. However, to the author´s ´ best knowledge, very few publications are available in the literature that discuss the problem of studying of the style features of the literary works with the help of images of the natural elements. The remainder of the paper is organized into three sections. Section I describes theoretical level of studying the stylistic characteristics of the work through the images of natural elements. Section II analyses features of the reception of images of natural elements by students during the initial reading of the work. Practical results are presented in Section III.